The nature, origin, and predictors of porosity in the Middle to Late Devonian Horn River Group of the Central Mackenzie Valley, Northwest Territories, Canada. (August 2022) - LaGrange, Maya T.; Atienza, Nicole Mae M.; Biddle, Sara K.; Harris, Brette S.; Fiess, Kathryn M.; Terlaky, Viktor; Konhauser, Kurt O.; Gingras, Murray K.
Abstract: The characterization of porosity is an essential step in the evaluation of resource-bearing porous media. Here, we focus on the Devonian Hare Indian and Canol Formations, two potential unconventional mudstone reservoirs, in a core from the Horn River Group of the Central Mackenzie Valley, Northwest Territories, Canada. By combining bulk porosity, low-pressure N2 adsorption, and scanning electron microscopy (SEM) results with composition and lithofacies datasets, we assess the porosity in these successions to understand pore types, size, distribution, degree of connectivity, and controls and predictors of porosity. Mineral matrix pores (interparticle and intraparticle), organic matter pores, and lithofacies-dependant natural fractures are present. All pore types display limited connectivity in two dimensions. Mineralogy is the most significant control on porosity with trends in porosity present among lithofacies. No relationship is observed between porosity and total organic carbon (TOC), suggesting that mineral matrix pores, rather than organic matter pores, are dominant in this unit. We compare these results to other mudstone reservoirs in North America and show that the Bluefish Member (Hare Indian Formation) and the Canol Formation are characterized by comparable bulk porosity, lower N2 mesopore volume, and higher quartz content relative to the other units considered. In contrast, compared to the other unconventional reservoir examples, the Bell Creek Member of the Hare Indian Formation exhibits lower quartz and higher clay content, average bulk porosity, and lower N2 pore volume. The results collectively suggest that high quartz and low clay content are the best predictors of porosity in the Horn River Group. Natural fractures may serve as flow pathways to induced fractures; however, these units lack the network of interconnected organic matter pores that can be present in other successions. Highlights: Helium porosimetry, N2 adsorption and desorption experiments, and SEM are used to evaluate porosity. Porosity controls and predictors are investigated through comparison to lithofacies, mineralogy, TOC, and thermal maturity. No relationship between TOC and porosity is observed, suggesting that mineral matrix pores are dominant. Mineralogy exerts the most significant control on porosity.